Prediction of the resistivity of YBa2Cu3O7-δ superconductor by a highly sensitive one-dimensional phononic crystal sensor. (December 2022) - Alrowaili, Z.A.; Gaber, Hisham Mohamed; Aljoufi, Lama Sh; Elsayed, Hussein A.; Taha, T.A.; Mehaney, Ahmed
Abstract: In this research, we have theoretically introduced a new application of one-dimensional (1D) phononic crystals (PnCs) manifested as a sensor for the variations in porosity ratios of a high Tc superconductor material (Ba2 Cu3 O7-δ ). Notably, there is a massive need for accurate detection of the changes in the porosity ratio of the YBa2 Cu3 O7-δ material due to the dependence of its resistivity and critical current density Jc as well on the porosity ratio. Meanwhile, the changes in the porosity ratio could be demonstrated by tuning a resonant mode in the transmission spectrum of the 1D PnC. Therefore, we considered the YBa2 Cu3 O7-δ as a defect layer inside the periodic design (Lead/Epoxy) N of the 1D PnC. Herein, the transfer matrix method (TMM) is used to calculate the transmission spectra of the proposed design. Our findings showed that the proposed sensor is capable of detecting and sensing the variations in the porosity ratio of YBa2 Cu3 O7-δ as well as indicating its mechanical properties with relatively high performance and sensitivity. Moreover, the obtained results have unfolded a very sensitive effect in the resonant peak position based on the physical properties of YBa2 Cu3 O7-δ . Since the position of the resonant peak is highly sensitive to the smallest changes in the porosity ratio. Finally, the investigated sensitivity and quality factor can reach the values of 75.04 kHz and 186.474, respectively, for a 1% change in the porosity of YBa2 Cu3 O7-δ . In a nutshell, it's a new way of correlating the mechanical properties of a porous high Tc superconducting material based on the porosity ratio that may be used in various industrial and technological applications.